SERS-based quantitative vertical flow assay using dual Au-Ag SERS nanoprobes - Jinhyeok Jeon; Ji-In Park; Chulhyun Lee (Results in Chemistry)
A surface-enhanced Raman scattering (SERS)-based vertical flow assay (VFA) platform was developed for the point-of-care testing (POCT) to perform multiplex diagnosis and distinguish each disease with similar symptoms (e.g., analysis of respiratory diseases including SARS-CoV-2, influenza and RSV). To evaluate the feasibility of multiplexing performance of SERS-VFA platform, vertical flow cartridges with 2 × 2 test areas on the nitrocellulose membrane and two different Raman reporter-labeled SERS nanoprobes were prepared, to detect samples including two different immunoglobulins (mouse IgG and rabbit IgG). For the preparation of SERS nanoprobes, we made use of the gold-silver/core–shell metal nanostructures for the local electromagnetic-field enhancement effect, and the Raman signal could be improved. SERS mapping images for each IgG in the sample were generated by measuring Raman peak position originated from each individual SERS nanoprobes. As a result, the quantitative analysis of each individual IgG could be performed at once, with a single sample. The detection limit for each rabbit IgG and mouse IgG was calculated as 0.030 μg/mL and 0.18 μg/mL, respectively. This result shows the SERS-based VFA platform could be of significant utility in multiplexed detection of chemical or biological targets.